2014
DOI: 10.3892/ol.2014.2822
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral carcinomatosis eleven years after advanced gastric cancer resection: A case report

Abstract: Bone metastasis is an uncommon event in advanced gastric cancer patients and bone metastases are rarely detected as isolated lesions. However, eleven years after treatment for locally advanced gastric cancer, including total gastrectomy followed by adjuvant chemotherapy, a 49-year-old female was admitted to the IX Division of General Surgery of the Second University of Naples (Naples, Italy) exhibiting severe progressive neurological symptoms. Magnetic resonance imaging indicated vertebral abnormalities, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Lastly, even if the majority of the GC recurrence occur into the first two years after curative resection, anecdotal cases of late relapses have been reported in the literature [ 72 , 73 ]. In particular, Iovino et al reported the case of a 49-year-old patient who showed a tumor relapse from GC after 11 years from the curative surgical resection [ 73 ].…”
Section: Clinical Overview On Bone Metastases From Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, even if the majority of the GC recurrence occur into the first two years after curative resection, anecdotal cases of late relapses have been reported in the literature [ 72 , 73 ]. In particular, Iovino et al reported the case of a 49-year-old patient who showed a tumor relapse from GC after 11 years from the curative surgical resection [ 73 ].…”
Section: Clinical Overview On Bone Metastases From Gastric Cancermentioning
confidence: 99%
“…Lastly, even if the majority of the GC recurrence occur into the first two years after curative resection, anecdotal cases of late relapses have been reported in the literature [ 72 , 73 ]. In particular, Iovino et al reported the case of a 49-year-old patient who showed a tumor relapse from GC after 11 years from the curative surgical resection [ 73 ]. The patient had severe neurological signs from a diffuse vertebral involvement and marrow infiltration without detection of any other metastatic lesions or primary tumor; the biopsy of the soft tissue near the lumbar vertebra confirmed the metastatic nature of the lesion, which spread from GC.…”
Section: Clinical Overview On Bone Metastases From Gastric Cancermentioning
confidence: 99%